PENGARUH LINGKUNGAN SEKOLAH TERHADAP MOTIVASI DAN HASIL BELAJAR SISWA DI SEKOLAH DASAR - Puspita, Tiara; Rahmi, Laili (ELSE (Elementary School Education Journal) : Jurnal Pendidikan dan Pembelajaran Sekolah Dasar, 2024)
This study aims to determine the condition of the school environment at SD Negeri 48 Pekanbaru, to find out whether there is a significant influence between the school environment on learning motivation and learning outcomes of students at SD Negeri 48 Pekanbaru. The method used in this study is the causal correlation study method. Where the sample consists of 30 students, namely class V of elementary school. The data collection technique uses a questionnaire while to analyze the data using the normality, homogeneity and hypothesis test formulas. This is evidenced in the t-test hypothesis test obtaining a value of 4.743 with a significant level of 0.000 <0.05. it can be concluded that the learning environment plays an important role in the learning process, especially on learning outcomes. Furthermore, there is a positive and significant influence between the learning environment and learning outcomes. This is evidenced in the t-test hypothesis test obtaining a value of 4.412 with a significant level of 0.000 <0.05. it can be concluded that the learning environment plays an important role in the learning process, especially on student learning motivation., meaning that there is a significant influence between the school environment on learning motivation and learning outcomes of class V students at SD Negeri 48 Pekanbaru.